AB0685 The incidence of giant cell arteritis in slovenia – prospective study. (12th June 2018) - Potočnik Pucelj, N.; Hocevar, A.; Ješe, R.; Rotar, Ž.; Pižem, J.; Hawlina, M.; Fakin, A.; Tomšič, M.
Abstract : Background: Giant cell arteritis (GCA) represents the most common vasculitis in adults over age of 50 years in Europe. Recently the diagnostic options greatly improved with the implementation of imaging techniques such as colour Doppler ultrasonography (CDS) and positron emission tomography-computed tomography (PET/CT). Objectives: The aim of our single centre prospective study was to determine the incidence of GCA in well-defined Slovenian region, based on the temporal artery (TA) biopsy (TAB) and/or the result of CDS and/or PET/CT. Methods: The study was conducted at University medical centre Ljubljana (UMC Ljubljana), that represents the only secondary/tertiary centre in a region, serving a population of 3 23 297 residents aged 50 years or more (1 76 104 females and 1 47 193 males). Patients with suspected GCA are referred either to the Department of Rheumatology, or in case of severe visual disturbances, to the Department of Ophthalmology. In the analysis we included all GCA cases diagnosed between 1 January 2012 and 31 December 2017. The diagnosis of cranial GCA (c-GCA) was established with the help of American College of Rheumatology (ACR) 1990 classification criteria, positive TAB and/or TA CDS. Cases of extracranial large vessel vasculitis (lv-GCA) were diagnosed using CDS of branches of the aortic arch and/or PET-CT. Results: During the six-year observation we identified 169 new GCA cases (66.3% females), with a median (IQR) age of 75.1 (68.6–80.0) years. Forty-two (24.8%) patients had lv-GCA, and the others had c-GCA. One-hundred and thirty-nine patients (24 lv-GCA and 115 c-GCA) fulfilled ACR 1990 classification criteria. The others patients had positive arterial CDS or PET-CT (18 CDS, 9 CDS and PET-CT, 3 PET-CT). TAB was performed in 119 patients and was positive in 88.2%. Clinical characteristics of our GCA cases are presented in table 1. The estimated annual incidence rate of GCA was 8.7 per 1 00 000 adults aged ≥50 years (95% CI 7.5–10.1), in c-GCA 6.5 per 100.000 adults aged ≥50 years (95% CI 5.5–7.8) and in lv-GCA 2.2 per 100.000 aged ≥50 years (95% CI 1.6–2.9). Conclusions: GCA is the most common vasculitis in adults aged 50 years or above, with an annual incidence rate of 8.7 per 100.000. c-GCA is nearly 3 times more common than lv-GCA. Disclosure of Interest: None declared